Palate Lung Nasal Clone (PLUNC), a Novel Protein of the Tear Film: Three-Dimensional Structure, Immune Activation, and Involvement in Dry Eye Disease (DED) - Schicht, Martin; Rausch, Felix; Beron, Martin; Jacobi, Christina; Garreis, Fabian; Hartjen, Nadine; Beileke, Stephanie; Kruse, Friedrich; Bräuer, Lars; Paulsen, Friedrich (Investigative Ophthalmology & Visual Science, 2015)
Palate Lung Nasal Clone (PLUNC) is a hydrophobic protein belonging to the family of surfactant proteins that is involved in fluid balance regulation of the lung. Moreover, it is known to directly act against gram-negative bacteria. The purpose of this study was to investigate the possible expression and antimicrobial role of PLUNC at the healthy ocular surface and in tears of patients suffering from dry eye disease (DED).Bioinformatics and biochemical and immunologic methods were combined to elucidate the structure and function of PLUNC at the ocular surface. Tissue-specific localization was performed by using immunohistochemistry. The PLUNC levels in tear samples from non-Sjögren's DED patients with moderate dry eye suffering either from hyperevaporation or tear deficiency were analyzed by ELISA and compared with tears from healthy volunteers.Palate Lung Nasal Clone is expressed under healthy conditions at the ocular surface and secreted into the tear film. Protein modeling studies and molecular dynamics simulations performed indicated surface activity of PLUNC. In vitro experiments revealed that proinflammatory cytokines and bacterial supernatants have only a slight effect on the expression of PLUNC in HCE and HCjE cell lines. In tears from DED patients, the PLUNC concentration is significantly increased (7-fold in evaporative dry eye tears and 17-fold in tears from patients with tear deficiency) compared with healthy subjects.The results show that PLUNC is a protein of the tear film and suggest that it plays a role in fluid balance and surface tension regulation at the ocular surface.
EVALuna2:4442